2016
DOI: 10.1080/1068316x.2016.1227816
|View full text |Cite
|
Sign up to set email alerts
|

Press coverage as a heuristic guide for social decision-making about sexual offenders

Abstract: We present two studies examining the role of the British press in\ud promoting heuristic-based decision-making about sexual crime. In\ud Study 1, 1014 press articles were used in order to examine the\ud role of the availability heuristic. That is, we used the recent highprofile\ud Jimmy Savile sexual offending scandal to investigate how\ud this case impacted upon press reporting of sexual crime. We\ud found a 295% increase in the frequency of sexual crime coverage\ud after this case, in addition to a 22:1 over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 27 publications
1
35
0
1
Order By: Relevance
“…These findings are in line with previous research suggesting that heuristics related to JSOs can contribute to harsher punishment (e.g., Harper & Hogue, 2017;Harris & Socia, 2016), yet they build upon previous research which has not explicitly measured the use of heuristics. Accordingly, these findings suggest that people who rely on heuristics as opposed to effortful, systematic decision-making strategies may be more likely to recommend harsher sentencing.…”
Section: Influence Of Control Variables (Usage Of Heuristics and Gesupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are in line with previous research suggesting that heuristics related to JSOs can contribute to harsher punishment (e.g., Harper & Hogue, 2017;Harris & Socia, 2016), yet they build upon previous research which has not explicitly measured the use of heuristics. Accordingly, these findings suggest that people who rely on heuristics as opposed to effortful, systematic decision-making strategies may be more likely to recommend harsher sentencing.…”
Section: Influence Of Control Variables (Usage Of Heuristics and Gesupporting
confidence: 91%
“…This the second known study to test for effects of race of the DSA and VSA in a juvenile sex offense case, and also to examine interaction effects between these variables, on a number of court outcome variables. Additionally, it built upon previous research suggesting that heuristics can impact decisions about punishment and SORN among JSOs (e.g., Harper & Hogue, 2017;Harris & Socia, 2016). Finally, the current study considered the impact of participant gender on suggested outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1970s [10,11], arguably the major starting point for research into sexual abuse, we have seen the emergence of several narratives linked to sexual abuse and how best to respond to it [1, 12••]. In today's socio-political climate, even before the advent of the #metoo movement [13], sexual offending was viewed as a high-profile issue that factored in political debates [14][15][16], media coverage [17][18][19][20], and public discourses [3,18,[21][22][23][24]. Often these public debates were, and still are, punitive in nature [25][26][27][28]29•] and viewed within a risk management framework [11,15,30].…”
Section: Introductionmentioning
confidence: 99%
“…This increased global sociopolitical recognition of sexual abuse corresponds to several interrelated factors, including increased investment in sexual violence education, increased reporting of historical cases, and a growing recognition that anyone can be a victim of sexual abuse which is, in part, seen as a consequence of the #METOO movement. In the last decade, in particular, we have seen a rise in the reporting of sexual abuse, current and historical, linked to institutions, sports clubs, charities, college campuses, and the church ( Australian Human Rights Commission, 2017 ; Tabachnick et al, 2016 ; Vertommen et al, 2018 ), and an increased media profile of sexual violence ( Harper & Hogue, 2017 ). However, sexual violence reporting and conviction rates vary widely between and within countries, dependent on the size, culture, and economic status of the country which makes determining a global prevalence rate difficult ( UNICEF, 2014 ; World Health Organization [WHO], 2014 ; see special edition of Sex Offender Treatment , McCartan, 2018 , for a broader international perspective).…”
mentioning
confidence: 99%